Analisis Kapasitas Sistem Drainase Parit Keramat di Kawasan Bandar Udara Supadio Kabupaten Kubu Raya Menggunakan HEC-RAS - Suwarman, Endang; Nurhayati, Nurhayati; Akbar, Aji Ali (Universitas Tanjungpura, 2026)
Supadio Airport has several drainage channels, including the Parit Keramat Drainage Channel. This channel has experienced narrowing due to household waste accumulation and sedimentation, leading to flooding in 2017 when the airport area was hit by extreme rainfall and high tides. As a result, 12 flight schedules were cancelled, and 36 flights were delayed (Kompas, 2017). To address this issue, an effective drainage system is necessary, especially in the runway, taxiway, and apron areas, to maintain aviation safety and security. The flood condition at Supadio Airport was analyzed using technical calculations and unsteady-flow simulations for a 10-year return period, based on tidal data calibration and instantaneous discharge in HEC-RAS. The drainage network in the study area was modeled based on topographic measurements of the existing channels. The Parit Keramat Channel is approximately 1,400 meters long. The HEC-RAS modeling results for the 10-year return period and tidal conditions show a significant impact on the existing channel condition. Most of the STAs (Stations) on the Parit Keramat Channel experienced flooding, with inundation heights ranging from 0.03 to 0.38 meters.